Legal Reasoning Judges in Determining Marriage Dispensation and Its Implications for Children's Rights in Indonesia - Aman; Gugun Gumilar (Universitas Islam Negeri Raden Intan Lampung, 2025)
Law No. 16/2019 stipulates the minimum age for marriage at 19 years for both men and women, and the Supreme Court Regulation No. 5/2019 on Guidelines for Adjudicating Marriage Dispensation Applications aims to prevent the increase of child marriage in Indonesia. However, in the past three years, cases of marriage dispensation at the Bandung High Religious Court have surged, with 90% of cases from 2020-2022 being granted. This study aims to analyze the judges' legal reasoning in granting marriage dispensation applications and its implications for children's rights in Indonesia. The study employs a qualitative method, combining library research and field research with a statutory and case approach, conducted at the Bandung High Religious Court. The findings indicate that judges' legal reasoning serves as a bridge between written law and the social reality faced by parties in cases. There are three aspects of judges' consideration in granting marriage dispensation applications: fulfillment of formal requirements, pregnancy out of wedlock, and the child's psychological readiness. The implications include an increase in the number of children dropping out of school, high risk of maternal mortality, risk of stunting, economic implications, and an increase in divorce rates